Optimization of Super-Resolution Features via Deep Learning Techniques - Hu, Yongkang; Jing , Chuyue; Li, Ziyuan; Liu, Xiao (Transactions on Computer Science and Intelligent Systems Research, 2024)
This manuscript delves into the pivotal role of feature optimization within the realm of deep learning-driven super-resolution techniques, a topic of considerable importance across diverse domains such as medical imaging and electron microscopy. The paper confronts the inherent challenges posed by deep learning in super-resolution tasks, including issues related to complexity, computational burden, and the paucity of model generalizability. It underscores the significance of feature optimization strategies, particularly the application of time-to-frequency transformation techniques such as wavelet and Fourier transforms, as well as attention mechanisms, in enhancing model efficiency and curtailing the demand on computational resources. A central theme of the discourse is the efficacy of amalgamating time-frequency separation methods — notably wavelet and Fourier transforms — with attention mechanisms in super-resolution endeavors. This integrated approach, termed multi-scale feature fusion, is lauded for its capacity to augment the model’s attentiveness to high-frequency details, which are crucial in super-resolution. This fusion strategy not only optimizes the allocation of computational resources but also elevates learning performance.